Tobacco Smoke Exposure, Urban and Environmental Factors as Respiratory Disease Predictors in Italian Adolescents - Bellisario, Valeria; Piccioni, Pavilio; Bugiani, Massimiliano; Squillacioti, Giulia; Levra, Stefano; Gulotta, Carlo; Mengozzi, Giulio; Perboni, Alberto; Grignani, Elena; Bono, Roberto (International journal of environmental research and public health, 2019)
Risk monitoring in childhood is useful to estimate harmful health effects at later stages of life. Thus, here we have assessed the effects of tobacco smoke exposure and environmental pollution on the respiratory health of Italian children and adolescents using spirometry and the forced oscillation technique (FOT). For this purpose, we recruited 188 students aged 6–19 years living in Chivasso, Italy, and collected from them the following data: (1) one filled out questionnaire; (2) two respiratory measurements (i.e., spirometry and FOT); and (3) two urine tests for Cotinine (Cot) and 15-F2t-Isoprostane (15-F2t-IsoP) levels. We found a V-shape distribution for both Cotinine and 15-F2t-IsoP values, according to age groups, as well as a direct correlation (p = 0.000) between Cotinine and tobacco smoke exposure. These models demonstrate that tobacco smoke exposure, traffic, and the living environment play a fundamental role in the modulation of asthma-like symptoms (p = 0.020) and respiratory function (p = 0.007). Furthermore, the results from the 11–15-year group indicate that the growth process is a protective factor against the risk of respiratory disease later in life. Lastly, the FOT findings highlight the detrimental effects of tobacco smoke exposure and urbanization and traffic on respiratory health and asthma-like symptoms, respectively. Overall, monitoring environmental and behavioral factors in childhood can provide valuable information for preventing respiratory diseases in adulthood.